Writing for science and engineering : papers, presentations and reports - Silyn-Roberts, Heather (Elsevier Science, 2013)
Learning how to write clearly and concisely is an integral part of furthering your research career; however, doing so is not always easy. In this fully updated and revised edition, Dr. Silyn-Roberts explains in plain English the steps to writing abstracts, theses, journal papers, funding bids, literature reviews, and more. The book also examines preparing seminar and conference presentations. Written in a practical and easy to follow style specifically for postgraduate students in Engineering and Sciences, this book is essential in learning how to create powerful documents.
Keywords: Technical writing.; elektronické knihy; electronic books